THE REFERRAL SYSTEM AND FEEDBACK PROCESS BY MEDICAL CONSULTANTS AT THE UNIVERSITY COLLEGE HOSPITAL, IBADAN. (2012)
Referral is an essential two-way process linking the three tiers of health care together. Lack of feedback is a common constraint to the proper functioning of the referral process and information is lacking on the factors which affect this process. This study was therefore designed to assess the knowledge, level of practice as well as the factors influencing the feedback process in the two-way referral system by medical consultants at the University College Hospital, Ibadan. A cross-sectional study of all medical consultants (82) who routinely receive referrals and actively provide specialized patient care at the University College Hospital, Ibadan was carried out. Using a self-administered questionnaire, information on socio-demographic characteristics, knowledge, practice and the factors affecting the two-way referral process was obtained from respondents. Validation was done by assessing all new patients records (1,207) in their clinics. Knowledge scores ranged between 0-8, scores of 0-4 were classified as poor knowledge and 5-8 as good knowledge. Chi-square test was used to determine association between categorical variables at 5% level of statistical significance. The mean age of the respondents was 46.5 7.5 years, 64.6% of the respondents were males and 51.2% had 15-24 years working experience as a doctor. The respondents included were surgeons (17.1%), dentists (15.9%), paediatricians (14.6%), physicians (12.2%), obstetrician and gynaecologists (9.8%), psychiatrists (6.1%), community health physicians (6.1%), haematologists (6.1%), radiotherapists (4.9%), ophthalmologists (3.7%), and otorhinolaryngologists (3.7%). Although 84.1% of the respondents had good knowledge of the two-way referral system, only 56.1% reported sending feedbacks. Evidence of feedbacks was available however in only 9.7% of case notes. The decision to send feedbacks was based on the reason for referral and detail of clinical information supplied by the referring healthcare provider as reported by 42.7% and 32.9% of the respondents respectively. Ignorance of the existence of the feedback system (14.6%), lack of commitment to the practice of sending feedbacks (13.4%), inadequate resources (11.0%) and a heavy patient load (9.8%) were identified by respondents as challenges to the two-way referral system. Most (97.6%) of the respondents believed that there was a need to improve the feedback system. Working experience was significantly and positively associated with sending of feedbacks. Feedback was also significantly associated with the existence of a coordinating system for referrals within the departments. Feedbacks were given more on outpatients than inpatients. Feedbacks from Ophthalmologists were significantly higher than those from other consultants. A feedback was also more likely if the information on the referral letter to the consultants contained detailed information. Knowledge about the two-way referral system was high in the study population but the feedback practice was poor. There is a need for a mechanism to monitor referrals, provide adequate resources and re-orientate medical consultants about the feedback.